2000
DOI: 10.1007/s11745-000-0576-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of mouse lipoxygenases: Identification of a subfamily of epidermal isozymes exhibiting a differentiation‐dependent mRNA expression pattern

Abstract: By using reverse transcription-polymerase chain reaction technology (RT-PCR) and Northern blot analysis, the tissue-specific mRNA expression patterns of seven mouse lipoxygenases (LOX)--including 5S-, 8S-, three isoforms of 12S-, 12R-LOX, and a LOX of an as-of-yet unknown specificity, epidermis-type LOX-3 (e-LOX-3)--were investigated in NMRI mice. Among the various tissues tested epidermis and forestomach were found to express the broadest spectrum of LOX. With the exception of 5S- and platelet-type 12S-LOX (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 41 publications
3
34
0
1
Order By: Relevance
“…Interestingly, some of the phenotypes observed in the p53+/ m mouse could be correlated to known physiological functions of gene products within the deletion. For example, the deleted region contains a cluster of 3 genes involved in lipid oxygenation, two of which are epidermal lipoxygenases that are expressed primarily in the mouse skin (Boeglin et al ., 1998;Jisaka et al ., 1997;Heidt et al ., 2000). Lipoxygenases have been shown to play important biological roles in mediating adipocyte and skin differentiation, inflammatory responses, and are also expressed in human hair roots (Baer & Green, 1993;Shillabeer et al ., 1998;Furstenberger et al ., 2002;Kantarci & Van Dyke, 2003;Yu et al ., 2003;Yu et al ., 2005).…”
Section: S Venkatachalam Department Of Biochemistry and Cellular Anmentioning
confidence: 99%
“…Interestingly, some of the phenotypes observed in the p53+/ m mouse could be correlated to known physiological functions of gene products within the deletion. For example, the deleted region contains a cluster of 3 genes involved in lipid oxygenation, two of which are epidermal lipoxygenases that are expressed primarily in the mouse skin (Boeglin et al ., 1998;Jisaka et al ., 1997;Heidt et al ., 2000). Lipoxygenases have been shown to play important biological roles in mediating adipocyte and skin differentiation, inflammatory responses, and are also expressed in human hair roots (Baer & Green, 1993;Shillabeer et al ., 1998;Furstenberger et al ., 2002;Kantarci & Van Dyke, 2003;Yu et al ., 2003;Yu et al ., 2005).…”
Section: S Venkatachalam Department Of Biochemistry and Cellular Anmentioning
confidence: 99%
“…Mutations in either 12R-LOX or eLOX-3 are associated with autosomal recessive congenital ichthyosis (these disorders will be discussed in detail in the review by Peter Elias) (105-107). Both 12R-LOX and eLOX-3 are localized to the differentiated stratum granulosum layer of the epidermis and convert arachidonic acid to hepoxilin-and trioxilin-like compounds that are believed to play a role in regulating keratinocyte differentiation (105,(108)(109)(110)(111). Moreover, very recent studies have shown that the creation of 12R-LOX-deficient mice results in a severe impairment in barrier function, with the mice dying soon after birth from a defective barrier (108).…”
Section: Jlr: Are There Other Pathways Of Fatty Acid Metabolism That mentioning
confidence: 99%
“…structural identity with differential epidermal expression (14,15) and a differing product spectrum: 8S-HETE and 9S-HODE (16) versus 15S-HETE and 13S-HODE (21). To explore the functions of these LOXs in keratinocytes, we established inducible expression lines and analyzed the effects of 8-LOX and 15-LOX-2 induction compared with the parental cell line 308 and the reverse Tet repressor expressing Cl20.…”
Section: -Lox-2 and Lox Induced Growth Inhibitionmentioning
confidence: 99%
“…Both enzymes are expressed in the skin of mice and humans but in different compartments of the epithelium. The expression of 15-LOX-2 is restricted to basal keratinocytes, whereas 8-LOX was found to be expressed in suprabasal keratinocytes (14,15). 8-LOX preferentially metabolizes AA to 8-HPETE compared with LA, yielding 9-HPODE (16,17).…”
mentioning
confidence: 99%